Ways and motivation usage of the game inteaching English - Темірбаева, Ж.Л.; Пазылова, А.А.; Кемал, Д. (My University, 2016)
This article deals with the methods of teaching English language in the Kazakh primary school, including the use of methods and techniques for the use of innovative technology and interactive whiteboard, how to use them. Made theoretical questions the use of game elements.
Keywords: a variety of games; psychological development; active participation; interest